2018
DOI: 10.1017/jfm.2018.591
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent channel flow of an elastoviscoplastic fluid

Abstract: We present numerical simulations of laminar and turbulent channel flow of an elastoviscoplastic fluid. The non-Newtonian flow is simulated by solving the full incompressible Navier-Stokes equations coupled with the evolution equation for the elastoviscoplastic stress tensor. The laminar simulations are carried out for a wide range of Reynolds numbers, Bingham numbers and ratios of the fluid and total viscosity, while the turbulent flow simulations are performed at a fixed bulk Reynolds number equal to 2800 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 67 publications
11
47
1
Order By: Relevance
“…Note that, the flow configuration and domain are the same used by Min et al (2001). Figure 3 highly dissipating schemes or with the inclusion of artificial numerical dissipation; in our simulation, we use the high-order WENO scheme for the advection of the conformation tensor and neglect any artificial dissipation, and we find good agreement of the deformation time history over the whole vortex merging process (Rosti & Brandt 2017;De Vita et al 2018;Rosti et al 2018c;Izbassarov et al 2018).…”
Section: Code Validationmentioning
confidence: 72%
“…Note that, the flow configuration and domain are the same used by Min et al (2001). Figure 3 highly dissipating schemes or with the inclusion of artificial numerical dissipation; in our simulation, we use the high-order WENO scheme for the advection of the conformation tensor and neglect any artificial dissipation, and we find good agreement of the deformation time history over the whole vortex merging process (Rosti & Brandt 2017;De Vita et al 2018;Rosti et al 2018c;Izbassarov et al 2018).…”
Section: Code Validationmentioning
confidence: 72%
“…The numerical code used in this work has been extensively validated in the past for turbulent flow simulations [35][36][37]. Here, we provide one more comparison with literature results for the specific case of a flexible filament.…”
Section: Validationmentioning
confidence: 99%
“…In turbulence, where the Reynolds stress is sufficient to break the plug, the behaviour of the YSF resembles a shear-thinning fluid (Güzel et al 2009a) characterized by a reduced wall-normal turbulence intensity. Recently, Rosti et al (2018) simulated the turbulent channel flow of an EVP fluid and observed that in the turbulent regime the friction factor decreases with increasing Bi, until the flow becomes laminar at high Bi.…”
Section: Other Aspects Of Flowing Ysfmentioning
confidence: 99%